From Business to Education: Action Learning in EFL Teacher Preparation Programs - Aya Khedr; Walaa El-Henawy; Jehan El Bassuony (Port Said Journal of Educational Research)
Action learning is a structured approach that enables small groups to work regularly and collectively on complicated problems, agreeing on actions, and learning as individuals and as a team while doing so. In this paper, action learning is cyclical process that values EFL Pre-Service teachers as both a source of knowledge and users of knowledge to generate new ideas and practices to collaboratively and through action learning sets work on issues that address EFL education and EFL learning environments. The purpose of this paper was to review literature and previous studies and research presenting the nature of action learning, its components, stage systems, process, and benefits. Besides, the paper sought to propose a framework to involve action learning in the EFL teacher preparation programs by presenting some recommendations for promoting the efficacy of EFL Pre-Service teacher programs at the faculties of education, as well as in the field of EFL education.